Perancangan Dan Implementasi Sistem Pendaftaran Online Pada TK Islam Baiturrahim Berbasis Website Menggunakan Metode Waterfall - Anwar Ramadhan, Rangga; Rhamdani Nasution, Muhammad; Saprudin (CV. Shofanah Media Berkah, 2025)
In today’s digital era, educational administration requires high efficiency and accuracy. TK Islam Baiturrahim previously relied on manual student registration methods, which caused various issues such as long queues, data entry errors, and limited access for student guardians. To address these problems, an online registration system was designed and implemented using a web-based platform and the Waterfall software development methodology. The system consists of two main modules: a user module (for student guardians) and an admin module (for school staff). Features developed include an online registration form, document upload, data validation, and applicant report generation. By applying the Waterfall approach, the system was built in stages—from requirements analysis, system design, and implementation, to testing and limited maintenance. The implementation results show that the system enhances the efficiency of the registration process, minimizes data errors, and improves accessibility for users. This system is expected to serve as a digital solution that supports the digital transformation of educational administration at the kindergarten level.